2009
DOI: 10.1073/pnas.0811402106
|View full text |Cite
|
Sign up to set email alerts
|

Changing meaning causes coupling changes within higher levels of the cortical hierarchy

Abstract: Processing of speech and nonspeech sounds occurs bilaterally within primary auditory cortex and surrounding regions of the superior temporal gyrus; however, the manner in which these regions interact during speech and nonspeech processing is not well understood. Here, we investigate the underlying neuronal architecture of the auditory system with magnetoencephalography and a mismatch paradigm. We used a spoken word as a repeating ''standard'' and periodically introduced 3 ''oddball'' stimuli that differed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…As discussed above, phonetic and phonological processes are clearly left lateralized in the mid-posterior STS, and we found no evidence for any consistent phonetic activity in the right temporal lobe in Phonetic/Phonological Analysis 1 . As discussed below, the results of Meta-analysis 2 in the present study, and prior electrophysiological evidence also support left hemisphere dominance for some aspects of categorical phoneme perception (Dehaene-Lambertz, 1997; Naatenen et al, 1997; Schofield et al, 2009). …”
Section: Discussionsupporting
confidence: 85%
“…As discussed above, phonetic and phonological processes are clearly left lateralized in the mid-posterior STS, and we found no evidence for any consistent phonetic activity in the right temporal lobe in Phonetic/Phonological Analysis 1 . As discussed below, the results of Meta-analysis 2 in the present study, and prior electrophysiological evidence also support left hemisphere dominance for some aspects of categorical phoneme perception (Dehaene-Lambertz, 1997; Naatenen et al, 1997; Schofield et al, 2009). …”
Section: Discussionsupporting
confidence: 85%
“…For example, sine-wave speech analogues that are initially perceived as nonspeech by listeners are perceptually less cohesive than synthetic speech (Remez, Pardo, Piorkowski, & Rubin, 2001), and are less likely to elicit categorical perception (Mattingly, Liberman, Syrdal, & Halwes, 1971); audiovisual integration (Kuhl & Meltzoff, 1982;Tuomainen, Andersen, Tiippana, & Sams, 2005) and to engage language regions in the brain (e.g., Scott, Blank, Rosen, & Wise, 2000;Schofield et al, 2009;Vouloumanos, Kiehl, Werker, & Liddle, 2001). Nonetheless, after minimal experience, such nonspeech stimuli can give rise to phonetic processing (e.g., trading relations, Best, Morrongiello, & Robson, 1981), allowing for the identification of linguistic messages (Remez, Rubin, Pisoni, & Carrell, 1981;Remez, Rubin, Berns, Pardo, & Lang, 1994;Remez et al, 2001), and engaging phonetic brain networks (Liebenthal, Binder, Piorkowski, & Remez, 2003;Meyer et al, 2005).…”
Section: Does Phonological Knowledge Apply To Nonspeech Inputs?mentioning
confidence: 99%
“…More recently, researchers have begun to use sophisticated analytic strategies such as functional and effective connectivity analysis to explore regional interactions for language (Bitan et al, 2005, 2006; Sonty et al, 2007; Allen et al, 2008; Leff et al, 2008; Schofield et al, 2009; David et al, 2011; Doesburg et al, 2012, 2015; Verly et al, 2014; Kadis et al, 2015; Xiao et al, 2016). In our recent MEG study of verb generation in children, we observed frequency dependent patterns of connectivity together with an increased number of suprathreshold effective (directed) connections with age, even though the extent of the network decreased and became increasingly left lateralized with age (Kadis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent MEG study of verb generation in children, we observed frequency dependent patterns of connectivity together with an increased number of suprathreshold effective (directed) connections with age, even though the extent of the network decreased and became increasingly left lateralized with age (Kadis et al, 2015). Others have used dynamic causal modeling (DCM) in fMRI to show that higher level language processing is relatively left lateralized, compared to basic sensory processes (Bitan et al, 2005, 2006; Sonty et al, 2007; Allen et al, 2008; Cao et al, 2008; Leff et al, 2008; Schofield et al, 2009; Xiao et al, 2016). In addition, involvement of subcortical structures in language processing has been supported by DCM for MEG and fMRI data related to auditory comprehension task (Booth et al, 2007; David et al, 2011).…”
Section: Introductionmentioning
confidence: 99%